Commonalities and differences of cluster policy of Asian countries; discussion on cluster open innovation - Arkadiusz Michał Kowalski; Marta Mackiewicz (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The article aims at investigating the commonalities and differences between cluster policies in selected East Asian and Southeast Asian countries: Thailand, Singapore, South Korea, and China, to outline the Asian model of a cluster policy. Clusters play a significant role in the economic development of these countries, and some practical experiences from Asia may be used to shape the cluster policy in the recovery process after the COVID-19 pandemic. The conducted research contributes to a better understanding of the cluster formation process, cluster development, and policy aims in the analyzed countries. In Singapore and South Korea, which are among the most innovative countries in the global economy, cluster policy is to a great extent part of innovation policy, focusing on facilitating the networking and cooperation between science and business, the flow of knowledge, transfer of technology, and developing innovative technologies of key economic importance. In China and Thailand, which are developing countries, there is a much stronger role of foreign direct investments, which take the central place in the cluster structure. However, one common characteristic of cluster development patterns in all the analyzed countries is a top-down approach, where clusters are emerging and developing mostly as a result of governmental decisions and public programs.
Keywords: 650; Asia; cluster policy; clusters